Mixed-ligand Cu(II) hydrazone complexes designed to enhance anticancer activity - Mo, QingYou; Deng, JunGang; Liu, Yani; Huang, GuiDong; Li, ZuoWen; Yu, Ping; Gou, Yi; Yang, Feng (European journal of medicinal chemistry, 2018)
The ligand quantity, ligand type, and coordination geometry have important influences on the anticancer activity of metal-based complexes. On the basis of the structures of previously reported 1:1 Cu(II)/ligand complexes ([Cu(L1)Cl]·2H2O 1a, [Cu(L2)Cl]·H2O 2a, and [Cu(L2)NO3]·H2O 3a), we subsequently designed, developed, and characterized a series of corresponding 1:1:1 Cu(II)/ligand/co-ligand complexes ([Cu(L1)(Py)Cl]·H2O 1b, [Cu(L2)(Py)Cl] 2b, and [Cu(L2)(Py)NO3] 3b), where L1 = (E)-N'-(2-hydroxybenzylidene)acetohydrazide, L2 = (E)-N'-(2- hydroxybenzylidene)benzohydrazide, and Py = pyridine. All six Cu(II) complexes were assessed for their in vitro anticancer properties against a panel of human cancer cells, including cisplatin-resistant A549cisR cell lines. Interestingly, we observed that the 1:1:1 Cu/ligand/co-ligand mixed-ligand Cu(II) complexes exhibited higher anticancer activity than the corresponding 1:1 Cu(II)/ligand complexes. In particular, the 1:1:1 Cu(II)/ligand/co-ligand complex 3b displayed the greatest toxicity toward several cancer cells with better IC50 (1.12–3.77 μM) than cisplatin. Further mechanistic explorations showed that the 3b complex induced DNA damage, thus resulting in mitochondria-mediated apoptotic cell death. Furthermore, the 3b complex displayed pronounced cytostatic effects in the MCF-7 3D spheroid model. [Display omitted] •We have synthesis of the 1:1:1 Cu(II)/ligand/co-ligand complexes.•The 1:1:1 complex had better antitumor activity than the corresponding 1:1 complex.•The 3b complex was active in 3D culture model.•We revealed the anticancer mechanism of the 3b complex.